Nazariyyatu al-Maqamat ‘Inda al-Syaikh ‘Abdul al-Qadir al-Jilaniy - Imroatul Istiqomah (Universitas Darussalam Gontor, 2017)
Maqamat is considered as the most important topic among the others in Sufism because it is the ethics and process of the heart and spirit that seeks to guide people for returning to Allah SWT. In “al-Ghunyah Lithalibi Thoriqi al-Haq ‘Azza wa Jalla,” al-Jilani—the Sufi figures who founded the Qadiriyah, the oldest and most widespread of the Muslim congregation— formulated the spiritual levels that a salik should take. Although al-Jilani does not call these spiritual levels as maqamat, but in the tradition of Sufism this is commonly called maqamat. Al-Jailani detailed the seven levels of the maqamat, namely al-taubah, al-zuhd, al-tawakkul, al-syukr, al-sabr, ar-ridhā and al-sidq. Al-taubah is considered as the first gate for a salik to get God’s blessings in this world and the hereafter. Al-zuhd did not mean to leave the world at all, as long as it did not neglect man from God and could help the religion and the hereafter. This is what distinguishes between Al-Jilani’s thought and the others which means al-zuhd is to leave the world.